Poetry and the making of the English literary past, 1660-1781 - Terry, Richard (Richard G.) (Oxford University Press, 2001)
Exploring how the English literary past was made, this book charts how antiquarians have unearthed the raw materials of the British tradition and how critics assigned the leading writers to canons of literary greatness.